x + x + 1 + x + 2 + x + 3 = -144x + 6 = 144x = 8x = 2
x(x4+x3+x2+x+1)
(X) x (4) x (8) x (12) = 384 X
no...why would it.... it equals 2x+9
= 18x + 13
Oh, dude, that's like a lot of x's and t's and some random letters thrown in there. So, technically, if you add all the x's, you get 7x, add all the t's, you get 3t, and the random letters are just there for decoration, I guess. So, the sum of x plus x plus x plus x plus x plus x plus x plus t plus t plus t plus jjakw is 7x + 3t + jjakw.
Oh, dude, you're hitting me with some math here. So, like, you've got 4 x's and 3 y's, right? So, you can simplify that expression as 4x + 3y. It's like organizing a messy room, but with letters and numbers.
4X
x=27
It is 123.99
x + x + 1 + x + 2 + x + 3 = -144x + 6 = 144x = 8x = 2
x+x+1+x+2+x+25=845 4x+28=845 4x=817 x=204.25
X= 5
x(x4+x3+x2+x+1)
When you add x plus x plus x, you are essentially adding three x terms together. This simplifies to 3x, which is the same as x multiplied by 3. So, x + x + x = 3x.
(X) x (4) x (8) x (12) = 384 X
yes cause like when u do x plus x plus x , its like 1 plus 1 plus 1 so its 3x just like 3